Maleic Anhydride Plant - Castillo, Mario D.; Eugenio, Benjamin M.; Filler, Juan C. (Diliman, Quezon City College of Engineering, 1964)
This plant design for the manufacture of maleic anhydride from benzene is designed with a capacity of twenty-five metric tone per twenty-four hour day. It requires a fixed capital investment of Php 1,601,000.00 and entails a total operating cost Php 10,500,000.00 per year.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants; Maleic anhydride